Parents’ Understanding About Children’s Bullying: Fall ConsumerStyles Survey, United States, 2017, 2018, and 2019 - Mercado, Melissa C. (Journal of interpersonal violence, 2024)
The purpose of this study was to explore U.S. parents’ and caregivers’ understanding about children’s bullying—what bullying is and how to address it. We analyzed 2017, 2018, and 2019 Fall ConsumerStyles online panel survey data from U.S. parents/caregivers of children ages 10 to 17 years (N = 1,516), including 20 items representing statements consistent or inconsistent with the bullying prevention evidence and best practices. Percentage of endorsement for each item and a summary measure of understanding about bullying were calculated. The association between low overall understanding about bullying and sociodemographic characteristics was explored. Most parents identified bullying as harmful (77%), repetitive (63%), and involving power imbalance (51%). At least half of parents answered 13 or more items (20 total) consistent with the bullying prevention evidence or best practices. Being male, non-Hispanic Black or Hispanic, having high school or less education, and small household size were associated with higher odds of low overall understanding about bullying. Awareness of parents’ understanding about bullying and how to appropriately address it is vital for bullying prevention. Findings can inform the strategic development of bullying prevention health messages for parents.